2011
DOI: 10.1111/j.1754-9434.2011.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Psychological Assessment: A Practice and Science in Search of Common Ground

Abstract: During the past 30 years, individual psychological assessment (IPA) has gained in use and in value to organizations in the management of human resources. However, even though IPA is considered a core competency for industrial–organizational (I–O) psychology, its practice is not without critics. This article is written not only to address several criticisms of IPA but also to discuss a variety of issues that must be taken into consideration if IPA is to advance as a major component of the I–O scientist–practiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 117 publications
(200 reference statements)
0
59
1
Order By: Relevance
“…While recent literature has given increased attention to individual assessment (McPhail & Jeanneret, 2011;Silzer & Jeanneret, 2011), additional research is needed to identify the practices that are most effective.…”
Section: Individual Assessment Meta-analysis 43mentioning
confidence: 98%
“…While recent literature has given increased attention to individual assessment (McPhail & Jeanneret, 2011;Silzer & Jeanneret, 2011), additional research is needed to identify the practices that are most effective.…”
Section: Individual Assessment Meta-analysis 43mentioning
confidence: 98%
“…Highhouse, 2008;Silzer & Jeanneret, 2011). Decades of research have demonstrated that a simple weighted average of test scores is generally as accurate, and sometimes more accurate, than clinical predictions (AEgisdóttir et al, 2006;Grove, Zald, Lebow, Snitz, & Nelson, 2000;Kuncel, Klieger, Connelly, & Ones, 2013).…”
Section: Personnel Assessment and Decisionsmentioning
confidence: 99%
“…In particular, IPA is widely used in executive selection (Silzer & Jeanneret, 2011), and IPA may provide higher validities for managerial occupations (Morris et al, 2015). Therefore, more favorable validity evidence might be expected for positions with greater managerial responsibility.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations